2023
DOI: 10.3390/antiox12030541
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Expression of Cardiac and Hippocampal Renin-Angiotensin and Kallikrein–Kinin Systems in Offspring from Mice Exposed to Alcohol during Gestation

Abstract: Prenatal alcohol exposure (PAE) impairs fetal development. Alcohol consumption was shown to modulate the renin–angiotensin system (RAS). This study aimed to analyze the effects of PAE on the expression of the renin–angiotensin system (RAS) and kallikrein–kinin system (KKS) peptide systems in the hippocampus and heart of mice of both sexes. C57Bl/6 mice were exposed to alcohol during pregnancy at a concentration of 10% (v/v). On postnatal day 45 (PN45), mouse hippocampi and left ventricles (LV) were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 95 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…10 The stronger MCA contraction in the offspring exposed to paternal preconception alcohol consumption was mainly via increased activities and expression of AT1R, especially its subunit1α rather than (ACE) and decreased expressions of AT2R in the offspring renal arteries. 21,37 Alcohol intake could directly increase plasma AngII concentrations in rats. 20 This study firstly demonstrated that paternal preconception alcohol changed the activities of RAS elements in the Ion channels, such as calcium channels and potassium channels, play an important role in AngII-mediated constriction in MCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The stronger MCA contraction in the offspring exposed to paternal preconception alcohol consumption was mainly via increased activities and expression of AT1R, especially its subunit1α rather than (ACE) and decreased expressions of AT2R in the offspring renal arteries. 21,37 Alcohol intake could directly increase plasma AngII concentrations in rats. 20 This study firstly demonstrated that paternal preconception alcohol changed the activities of RAS elements in the Ion channels, such as calcium channels and potassium channels, play an important role in AngII-mediated constriction in MCA.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the present study uncovered higher circulating AngII concentrations in the alcohol offspring, which might contribute to the potentiated vascular contraction and indicated the activation of RAS. Maternal alcohol consumption during pregnancy increased expressions of AT1αR and angiotensin‐converting enzyme (ACE) and decreased expressions of AT2R in the offspring renal arteries 21,37 . Alcohol intake could directly increase plasma AngII concentrations in rats 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation